2015
DOI: 10.1108/jpmh-04-2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

Peer support as a resilience building practice with men

Abstract: Structured Abstract:Purpose This paper presents findings from an evaluation of a mental health resilience intervention for unemployed men aged 45-60. The paper examines the place of facilitated peer support within a men's mental health programme, and explores implications for resilience building approaches for men. DesignThe paper draws on before and after survey data and qualitative interviews, to report results concerning effectiveness in changing men's perceived resilience, to consider project processes con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…Robinson et al performed a qualitativeinterventional study on 21 unemployed men by organizing peer support sessions and then conducting structured interviews. The results suggested a significant improvement in the perceived score of the resilience of the subjects (31). Although the interventions executed in the above studies structurally differ from the one used here, the results of all the three studies corroborate that the implementation of interventions with the help of a peer educator could bring about a significant difference in the score of resilience.…”
Section: Discussionsupporting
confidence: 63%
“…Robinson et al performed a qualitativeinterventional study on 21 unemployed men by organizing peer support sessions and then conducting structured interviews. The results suggested a significant improvement in the perceived score of the resilience of the subjects (31). Although the interventions executed in the above studies structurally differ from the one used here, the results of all the three studies corroborate that the implementation of interventions with the help of a peer educator could bring about a significant difference in the score of resilience.…”
Section: Discussionsupporting
confidence: 63%
“…In contrast, an Indian study found that when young men experienced a high level of peer bullying, this leads to a low level of resilience (Narayanan & Betts, 2014). To summarise, a high level of peer support may lead to a high level of academic resilience (Robinson, Raine, Robertson, Steen, & Day, 2015).…”
Section: Introductionmentioning
confidence: 92%
“…Two principles underpinning this model are that (a) men don’t “go it alone” but instead connect with other men to engage mutual help and (b) male peer support models embody critical and complex approaches to gender ( Seebohm, Munn-Giddings, & Brewer, 2010 ). Work with returned soldiers ( Westwood, McLean, & Cave, 2010 ), men’s smoking cessation ( Bottorff, Johnson, Irwin, & Ratner, 2000 ), and men’s mental health ( Robinson, Raine, Robertson, Steen, & Day, 2015 ) indicates that men have the capacity within groups and through virtual platforms to effectively advance the health and illness practices of other men. Applying such approaches to men’s severe depression and suicidality might concurrently reduce some of the pressure on women amid mobilizing men’s peer-supported self-management strategies to reduce male suicide.…”
Section: Discussionmentioning
confidence: 99%